2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support System to Project Software Management

Abstract: This paper presents a Decision Support System (DSS)to project software management that uses a hybrid methodology. This is based on a combination of linear programming method, for assignment of tasks, and the task management method, Scrum. This proposal aids in management and optimization of the time of completion of the project or sprint without removing the inherent flexibility of agile methodologies. A support tool was developed to assist in the applicability of DSS. It is concluded that the DSS proposed can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The authors further suggested that there is a need to explore other factors related to estimation and development of a system that can predict effort as well as cost. In addition, Vilmar and Marcele [27] proposed a decision support system using scrum for effective handling of software projects. Their system facilitates the scrum master for time estimation of upcoming software projects or sprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors further suggested that there is a need to explore other factors related to estimation and development of a system that can predict effort as well as cost. In addition, Vilmar and Marcele [27] proposed a decision support system using scrum for effective handling of software projects. Their system facilitates the scrum master for time estimation of upcoming software projects or sprint.…”
Section: Literature Reviewmentioning
confidence: 99%